A haptics–based virtual simulation system for product design. (3rd December 2012) - Wang, Jinling; Lu, Wen F.
This paper aims to develop a haptics–based virtual simulation system for product design. To fully reach the potential of such a system, the modelling methods of the user–product interaction should be based on physics to enable users to feel the physical behaviours of various products. The key challenge is the balance between the heavy computational load and the high update rate for haptic feedback. In this paper, the modelling of rigid and deformable objects for haptics–based simulations is developed, including button click and vibration feeling as well as the interaction with heterogeneous deformable material. The commercial haptic device PHANToM Desktop from SensAble Technologies is integrated with the models into the implemented prototype system. It is validated that the proposed simulation system can allow users to experience and manipulate virtual objects in cyber space. The simulation results demonstrate that the proposed modelling methods are computationally efficient to provide real–time haptic feedback.